2016
DOI: 10.1002/jso.24307
|View full text |Cite
|
Sign up to set email alerts
|

Tumor regression grade in gastric cancer: Predictors and impact on outcome

Abstract: Few gastric cancers demonstrate histologic response to neoadjuvant chemotherapy. While TRG may be a valid marker for treatment response, its predictive value and clinical application in gastric cancer remains unclear. J. Surg. Oncol. 2016;114:434-439. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 27 publications
1
37
1
Order By: Relevance
“…Differently, in two recent retrospective works regarding predictor factors of survival after perioperative MAGIC-style chemotherapy, TRG1 rates were lower (17%) (17,18). In Becker's analysis TRG was significantly correlated with survival, while in Schmidt's study TRG does not reveal itself as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 81%
“…Differently, in two recent retrospective works regarding predictor factors of survival after perioperative MAGIC-style chemotherapy, TRG1 rates were lower (17%) (17,18). In Becker's analysis TRG was significantly correlated with survival, while in Schmidt's study TRG does not reveal itself as an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 81%
“…In the current study, 12/62 (19.4%) patients had a complete or marked response to neoadjuvant chemotherapy, and only 4/62 (6.5%) exhibited a complete response on final pathology. In other studies, tumor responses were also low, with less than 25% of patients with a significant response while >50% of patients had minimal response (29)(30)(31). Many of these reports also failed to show a statistically significant relationship between response to neoadjuvant therapy and survival.…”
Section: Discussionmentioning
confidence: 93%
“…Comparison with initial clinical and pathologic stages revealed downstaging of T stage in 66.7% of patients (32/48) and downstaging of N stage in 45.8% of patients (22/48) (Table ). Although there is still no universally accepted grading system for pathologic regression, numerous studies have shown that the degree of pathologic response is a vital prognostic marker of local recurrence, distant metastases, and long‐term outcomes in locally advanced gastric cancer after neoadjuvant therapy . More importantly, pathologic response can guide clinical decisions about surgical strategies, adjuvant therapy, and long‐term surveillance .…”
mentioning
confidence: 99%